Transtornos alimentares na infância e na adolescência - Gonçalves, Juliana de Abreu; Moreira, Emilia Addison M.; Trindade, Erasmo Benício S. de M. [UNESP]; Fiates, Giovanna Medeiros R. (FapUNIFESP (SciELO), 2013)
Objective: To discuss eating disorders in children and adolescents regarding their characteristics and risk factors. Data sources: Articles were searched in the PubMed and ScieLO databases, combining the terms 'children', 'adolescents', 'eating behavior', 'eating disorder', 'bulimia', and 'anorexia', both in Portuguese and in English. Studies published between 2007 and 2011 were retrieved and 49 articles that assessed eating behavior and disorders, nervous anorexia and bulimia, and non-specific eating disorders were selected. Data synthesis: Eating disorders, especially non-specific ones, were common during childhood and adolescence. The presence of such disorders was attributed mainly to family environment and exposure to the media. Eating disorders were frequently followed by psychological comorbidities. Conclusions: Among the risk factors for eating disorders, social and family environment and the media were the most important ones. The influence of the media and social environment has been related to the worship of thinness. As to family environment, mealtimes appeared to be fundamental in shaping eating behavior and the development of disorders. Eating disorders were associated with nutritional problems (growing impairment and weight gain), oral health (cheilitis, dental erosion, periodontitis, and hypertrophy of salivary glands), and social prejudice.
Eating disorders in childhood and adolescence
Keywords: Adolescent; Anorexia; Bulimia; Child; Feeding behavior; Food habits